Friction and wear characteristic of organic brake pads material. (February 2019) - Pinca-Bretotean, C; Craciun, A L; Josan, A; Ardelean, M
Abstract: Many parts of motor vehicles contribute actively or passively to increasing operation performance. The safety is closely related to the effectiveness of the braking system. Due to the fact that the automotive industry is a branch of economics that uses products obtained in almost all other industries, the current concerns are directed towards the application of the latest research in the field of modern materials and technologies in all fields involved in the manufacture of motor vehicles. The proposed and carried of this paper aimed to presented, obtained, characterize and test some organic composite materials, designed to make brake pads for the braking systems of small cars with medium performances. The experimental research strategy included the determination of the functional characteristics of organic composite materials developed. In this respect, experimental laboratory determinations were carried out on the friction and wear of composite materials produced, using standardized test methods. The knowledge of these elements provides the possibility of pertinent assessments on the durability in operation of the composite material used for the manufacture of brake pads.